Assessment of proprioceptive and kinesthetic memory in shoulder joint using KEMTAI software system - Nenad Nedović; Stevan Jovanović; Danilo Vujčić; Slavica Mutavdžin Krneta (Exercise and Quality of Life)
Proprioception and kinesthesia refer to the sense of joint position and movement, assessable through joint position sense (JPS). We evaluated the potential of the KEMTAI software system in tracking and quantifying shoulder movement by examining 40 subjects (ages 22-68) divided into three age groups. Subjects, blindfolded, performed shoulder flexion, stopped on voice command and by their own at predefined angles measured by the software. Our findings indicated no significant differences in JPS accuracy across age groups, although precision improved with external cues, and a decline in JPS memory over short intervals was observed, suggesting further exploration is needed.